Analisis Praktik Bisnis E-Commerce dalam Perspektif Etika Bisnis Islam - Ahrozi, Ahmad; Nuraeni, Eni (Masoem University, 2025)
With the development of technology, business activities have shifted from face-to-face to online (e-commerce). These transactions eliminate needs for consumers to meet directly with the producer or seller and do not require them to see the product in person. E-commerce transactions are conducted through social media or marketplaces. Transactions via social media include Facebook, Instagram, TikTok, and others. Marketplace transactions can be conducted through Shopee, Tokopedia, Lazada, and others. This study used a descriptive qualitative approach. The purposively selected sample consisted of online sellers in the area around Tegal Gubug Market, Arjawinangun District, Cirebon Regency. Tegal Gubug Market is the largest clothing market in Indonesia. The results of this study indicate that the business practices carried out by e-commerce sellers in the area around Tegalgubug Market, Arjawinangun District, Cirebon Regency have not fully implemented Islamic business ethics because there are still those who do things that are not in accordance with sharia, including being dishonest (shiddiq) in displaying photos of products that are actually owned by other people, not being trustworthy (amanah) in sending products according to orders, being smart (fathonah) and being able to follow campaign programs and make independent promotions and not all sellers convey (tabligh) product descriptions as they are.